0687 Sleep Disorder Symptom Endorsement by Age. (12th April 2019) - Boyle, Julia T; Williams, Natasha; Grandner, Michael; Vargas, Ivan; D'Antonio, Breanna; Seewald, Mark; Muench, Alexandria; Ellis, Jason; Posner, Donn; Rosenfield, Bradley; DiTomasso, Robert A; Perlis, Michael L
Abstract: Introduction: It is widely held that the likelihood of having a sleep disorder increases with age and that this is especially true of Insomnia, OSA, and RLS. Few studies, however, have been conducted that concurrently assess how symptoms vary with age while simultaneously taking into account multiple sleep disorders. The present analysis evaluates the prevalence of ten sleep disorders symptoms across four age cohorts. Methods: An archival analysis was conducted on an existing database of 4, 206 individuals who completed an on-line screening survey atwww.sleeplessinphilly.com . Subjects were grouped into four age categories (matched for race, BMI, and gender): Young Adults (YA[18-29]), Adults (A[30-44]), Middle Aged Adults (MA[45-65]) and Older Adults (OA[65-89]). The sleep disorders symptoms assessed were for insomnia (problems with SL, WASO or EMA), snoring, [witnessed apneas], gasping, AM headaches, EDS, sleep attacks, muscular weakness with strong emotion, nightmares, and unpleasant sensations in the legs near bedtime. Contingency and Chi-Square analyses were used to assess for age group differences. Results: Each age group was comprised of 180 subjects (total n=720, 55% female). There were significant age related differences (and linear trends) for: Insomnia ([All:85.8%]; [YA:73.3%]<[A:87.8%]=[MA:88.3%]<[OA:93.9%], p < 0.001); Snoring ([All:44.2%]; [YA:26.7%]<[A:41.1%]<[MA:55%]>[OA:53.9%], p < 0.001); and Witnessed apneas ([All: 28.1%]; [YA:17.8%]<[A:27.2%]=[MA:33.3%]=[OA:33.9%], p = 0.002). There were age group differences (but not linear trends) for: Nightmares ([All: 50.7%]; [YA:57.2%]=[MA:57.2%]=[A:48.3%]>[OA:40%], p = 0.002); Headaches ([All:31.4%]; [A:43.3%]>[MA:32.2%]=[YA:29.4%]>[OA:20.6%], p < 0.001); and Muscular weakness ([All: 25.7%]; [A:30.6%)=[YA:28.9%)=[MA:25.6%)>[OA:17.8%], p = 0.028). There were no significant age differences for EDS (All:53.6%), gasping (All:20.6%), RLS symptoms (All:22.1%), or sleep attacks (All:17.2%). Conclusion: While sleep disorders symptoms vary with age, linear trends appear to be evident only for insomnia and the OSA symptoms of snoring and witnessed apneas. Note: One limitation of the present analysis is that the sample was populated by subjects with sleep complaints. This resulted in higher overall prevalence than is typical in population data. Support (If Any): Perlis NIH:R01AG041783;K24AG055602;R01AT003332